Between concepts and thought: digital technologies and temporal relationality. (September 2020) - Kessler, Oliver; Lenglet, Marc
This article advances the argument that the acceleration of practices introduced by digital technologies also impact key concepts of social theory. Digital technologies not only give rise to new concepts, but they also reconfigure our entire socio-political conceptual vocabulary. In particular, this acceleration reorganises the relationship between the spatial and temporal dimensions of political concepts. As a consequence, our spatially defined understanding of authority, hierarchy or relation underestimates the repercussions of shifting temporalities. This article pursues this shift from space to time and outlines how temporal relationality is gradually impacting the representations and images we live by.